The effects of inhibition of fatty acid oxidation in suckling newborn rats. - Pégorier, J P (1977)
Inhibition of fatty acid oxidation with pent-4-enoate in suckling newborn rats caused a fall in blood [glucose] and blood [ketone bodies] and inhibition of gluconeogenesis from lactate. Glucose utilization was not increased in newborn rats injected with pent-4-enoate. Active fatty acid oxidation appears to be essential to support gluconeogenesis and to maintain normal blood [glucose] in suckling newborn rats.